Longitudinal cellular and humoral immune responses following COVID-19 BNT162b2-mRNA-based booster vaccination of craft and manual workers in Qatar - Thomas, Remy; Zaqout, Ahmed; Meqbel, Bakhita; Jafar, Umar; Vaikath, Nishant N.; Aldushain, Abdullah; Naik, Adviti; Shaath, Hibah; Al-Akl, Neyla S.; Adam, Abdi; Moussa, Houda Y. A.; Shin, Kyung C.; et al. (Frontiers in Immunology, 2025)
BackgroundIn March 2020, the rapid spread of SARS-CoV-2 prompted global vaccination campaigns to mitigate COVID-19 disease severity and mortality. The 2-dose BNT162b2-mRNA vaccine effectively reduced infection and mortality rates, however, waning vaccine effectiveness necessitated the introduction of a third vaccine dose or booster.AimTo assess the magnitude and longevity of booster-induced immunity, we conducted a longitudinal study of SARS-CoV-2 specific cellular and humoral immune responses among Qatar’s vulnerable craft and manual worker community. We also investigated the impact of prior naturally acquired immunity on booster vaccination efficacy.MethodsSeventy healthy participants were enrolled in the study, of whom half had prior SARS-CoV-2 infection. Blood samples were collected before and after booster vaccination to evaluate immune responses through SARS-CoV-2 specific ELISpots, IgG ELISA, neutralization assays, and flow cytometric immunophenotyping.ResultsT cell analysis revealed increased Th1 cytokine responses, marked by enhanced IFN-γ release, in recently infected participants, which was further enhanced by booster vaccination for up to 6-months. Furthermore, booster vaccination stimulated cytotoxic responses in infection-naïve participants, characterized by granzyme B production. Both natural SARS-CoV-2 infection and booster vaccination induced robust and durable SARS-CoV-2 specific humoral immune responses, with high neutralizing antibody levels. Prior natural infection was also linked to an increased number of class-switched B cells prior to booster vaccination.ConclusionsThese findings underscore the importance of booster vaccination in enhancing anti-viral immunity across both infection-naïve and previously infected individuals, enhancing distinct arms of the anti-viral immune response and prolonging naturally acquired immunity.